GENDER RESPONSIVENESS IN THE VIOLENCE AGAINST WOMEN PREVENTION PROGRAM IN BANDUNG CITY: AN ANALYSIS OF THE IMPLEMENTATION OF SDGS 5-BASED DP3A - Suryaatmaja, Muhammad Naufal; Indraswuri, Dinda Ayu; Dolianshi, Huri Putri; Saefulrahman, Iyep (LPPM Univ. Ibn Khaldun Bogor, 2026)
Violence against women remains a priority issue in the context of local government and is one of the indicators for achieving SDGs 5. The Bandung City Government, through the DP3A (Regional Development Planning Agency), implements the Prevention of Violence Against Women Program to strengthen efforts to protect and fulfill women's rights. This study aims to analyze the implementation of this program by assessing the level of gender responsiveness in the policy process and its implementation. The research approach uses a qualitative descriptive-evaluative method through interviews and a review of official documents such as the Strategic Plan (RENSTRA), program reports, and data on gender-based violence. The analytical framework uses David Easton's policy system model and the Gender Mainstreaming (PUG) perspective. Initial results indicate that the policy has a strong regulatory basis and is aligned with the mandate of SDGs 5. However, its implementation still faces challenges such as limited gender-responsive budgets, cross-sectoral coordination, and the use of gender-disaggregated data. These findings indicate a gap between policy formulation and implementation, necessitating the strengthening of more gender-responsive service design.